Impact of circadian rhythm preference on performance in China’s standardized residency training: The mediating role of loneliness - Yi Yang; Yanxia Zhu; Jianqiang Ni; Jiang Yan; Jun Yin; Le Yang; Hao Li (PLoS ONE, 2025)
Objective This study aimed to clarify how circadian rhythm preference influences academic performance within the evolving framework of standardized residency training in China, where research on residents’ psychological adaptation and social support remains limited. The main objective was to explore the relationship between individual chronotypes and standardized training performance, as well as the potential mediating effect of loneliness levels. Methods Basic information of residents who completed standardized training at the First Affiliated Hospital of Soochow University was retrospectively collected, including baseline information such as gender, place of study, and program type. Participants’ chronotypes and loneliness levels were evaluated using the Morningness-Eveningness Questionnaire-Self-Assessment and the University of California, Los Angeles Loneliness Scale. We then explored the relationships among chronotype, loneliness level, and academic performance using generalized linear modeling and mediation analysis. Results A total of 198 participants who had completed their residency training were included, among whom 93 (47.0%) achieved relatively higher final scores. After adjusting for confounding factors, the generalized linear models revealed significant associations between MEQ-SA scale (OR: 0.811, 95% CI: 0.770–0.855, p < 0.001), UCLA Loneliness scale (OR: 1.793, 95% CI: 1.076–1.323, p = 0.001), and the standardized training grades. Furthermore, mediation analysis indicated that loneliness level acted as a mediator in the association between chronotypes and training achievements (mediating role = 55.66%). Conclusion Unlike adolescents, residents in standardized training with an evening chronotype achieved higher final grades. Notably, loneliness significantly mediated this relationship, challenging conventional views on social isolation and learning. These findings underscore the need for further research to clarify underlying mechanisms and potential interventions in medical training.